STRATEGI BISNIS PT. PERIKANAN SAMODRA BESAR CABANG BENOA-BALI UNTUK MENCAPAI TARGET EKSPOR - NYOMAN RUSMINI (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2003)
This research aim to formulate business strstegy of PT Perikanan Samodra Besar ofBali-Benoa branch to achieve export targets. Choises of the research location use thepurposive methods. The data analysis use Strengths, Weakness, Opportunities Threats(SWOT) methods, namely to analys the firm internal and external factors in framework toformulate axatly business strategy. SWOT analysis to result four combination of strategyi.e.: Strengths-Opportunity (SO) strategy is a strategy use strengths to utilize the opportunity,Strengths-Threats (ST) strategy is a strategy use strengths to overcome the threaths,Weakness Opportunity (WO) strategy is a strategy to minimize the weakness to utilizeopportunity, and Weakness-Treaths (WT) strategy is a strategy to minimize the weaknessand overcome the threaths.Based on the result analysis of the internal and external factors, PT. PerikananSamodra Besar Benoa branch has the competitive advantage compared their main competitorin term business experience, export market share, available the facility completely and thefamous of firm name. Yet, the corporation less advantage in product quality, productdiversification and market segmetation.Strategy can be formulated to achieve the export target are: SO strategy i.e.: toincrease volume export, selves product as well as buying other firm products, to increase theproduct though to add the fishing at the own ships and reevaluate the fishing numbers thatsucces to get the weight and kind of the good fishes. ST strategy i.e.: to keep the harmonyrelationships with employees and to expand the market. WO strategy i.e.: to inctrease thepromotion through internet medium, product diversification with make the fillet product andimplemented the Hazzard Analysis Critical Control Point (HACCP) plan namely to monitorand control sistematicaly as long as production process untill the end product so that canresult the good quality products. WT strategy i.e.: to increase the services towardsconsumers and human resources training continously.